2015
DOI: 10.12691/jfnr-3-1-11
|View full text |Cite
|
Sign up to set email alerts
|

High Anti-oxidative and Lipid-lowering Activities of Flavonoid Glycosides-rich Extract from the Leaves of <i>Z</i><i>an</i><i>t</i><i>h</i><i>o</i><i>xyl</i><i>u</i><i>m</i><i> </i><i>b</i><i>u</i><i>n</i><i>geanum </i>in Multi-system

Abstract: Epidemiological studies observed that Zanthoxylum bungeanum leaf, a popular vegetable in China, could interfere progression of cardiovascular diseases, especially hyperlipidemia. In the work, the pharmacological properties of Z.bungeanum leaves extract (ZLE) containing isovitexin, vitexin, hyperoside, rutin, isoquercitrin, foeniculin, trifolin, quercitrin, astragalin, and afzelin were investigated using multi-system such as mice organ tissue, HepG2 cell and apoE-/-mice. ZLE exhibited a stronger activity of sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
5
0
2
Order By: Relevance
“…A number of evidence have confirmed that free radicals in the human body is a crucial etiological factor contributing to the lipid peroxidation which leads to several chronic diseases, SOD is the first line of defense against the oxidative damage. Our work suggested that GF could prevent and treat oxidative stress and hypercholesterolemia induced by free radicals and lipid peroxidation mainly owing to the absence of accumulation of superoxide anion radicals, which was consistent with the previous reports [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A number of evidence have confirmed that free radicals in the human body is a crucial etiological factor contributing to the lipid peroxidation which leads to several chronic diseases, SOD is the first line of defense against the oxidative damage. Our work suggested that GF could prevent and treat oxidative stress and hypercholesterolemia induced by free radicals and lipid peroxidation mainly owing to the absence of accumulation of superoxide anion radicals, which was consistent with the previous reports [15].…”
Section: Discussionsupporting
confidence: 93%
“…Therapeutic effects of food and herbal medicines rich in GF have led to a rapid growth of knowledge in this area [8,9,10,11]. The natural flavonoids from many plants have also been reported to have anti-inflammatory, antioxidative, anti-hypercholesterolemic and anti-atherosclerotic activities [12,13,14,15]. To the best of our knowledge, the effect of GF from Artocarpus altilis on hypercholesterolemia related to its antioxidative property has not been symmetrically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that some flavonoids exhibit lipid-lowering activity and decrease LDs in adipocytes through lipolysis by different mechanisms reducing LDs' number. [26][27][28] Fat tissues were dissected from control larvae and stained with a lipophilic dye (BODIPY 493/503) to detect neutral lipids (Figure 1a). In the fat body cells, all the flavonoids induced a decrease of the percentage of cytoplasm area occupied by LDs, from 35.15% of the control to 30.17%, 32.56%, 26.82%, and 29.04% in the genistein, xanthohumol, and isoquercetin exposure, respectively (Figure 1b).…”
mentioning
confidence: 99%
“…O extrato aquoso das partes aéreas de Pistacia lentiscus ricas em flavonoides e ácido gálico, na concentração de 10 µg/mL inibiu em 74% a peroxidação lipídica induzida por ferro em células de rato (Ljubuncic et al 2005). Extrato de folhas de Zanthoxylum bungeanum com presença dos flavonoides quercitrina e afzelina demonstrou que concentrações a partir dos 250 µg/mL inibem o dano oxidativo induzido por radicais livres e peroxidação lipídica (Ma et al 2015). Kinjo et al (2006) A diferença na resposta entre as linhagens pode ser devida à capacidade metabólica que a HepG2 conserva.…”
Section: Ensaios Associação Metais-compostos Em Hepg2unclassified
“…Médias com a mesma letra não diferem significativamente entre si (p>0,05).Fonte: produção do autor.Porém, a avaliação feita através do MTT não mostrou citotoxidade contra HepG2 após 24 h de incubação a 1, 10 e 50 µM, nem de suas formas heterosídicas isoquercitrina e rutina (quercetina-3-O-rutenosídeo) segundo o avaliado porVrba et al (2012).Já as substâncias isoladas no presente estudo e os extratos vegetais que contêm quantidades consideráveis delas, apresentaram um comportamento biológico diferente. O extrato metanólico das folhas de Zanthoxylum bungeanum contendo predominantemente flavonoides com destaque para quercitrina e afzelina, foi avaliado contra HepG2 no ensaio de MTT em concentrações de 100 a 1000 μg/mL, sem mostrar citotoxidade após 24 de exposição(Ma et al 2015). Tanto em PC12 quanto em HepG2, o extrato vegetal de Pistacia lentiscus rico…”
unclassified